Interannual Climate Variability of the Past Millennium from Simulations - YANG Kai-Qing JIANG Da-Bang (Atmospheric and oceanic science letters = Daqi-he-haiyang-kexue-kuaibao, 2015)
The interannual variability of global temperature and precipitation during the last millennium is ana- lyzed using the results of ten coupled climate models participating in the Paleoclimate Modelling Intercomparison Project Phase 3. It is found that large temperature （precipitation） variability is most dominant at high latitudes （tropical monsoon regions）, and the seasonal magnitudes are greater than the annual mean. Significant multi-dec- adal-scale changes exist throughout the whole period for the zonal mean of both temperature and precipitation variability, while their long-term trends are indistinctive. The volcanic forcings correlate well with the temperature variability at midlatitudes, indicating possible leading drivers for the interannual time scale climate change.